The role of RNA G‐quadruplexes in human diseases and therapeutic strategies. (12th September 2019) - Kharel, Prakash; Balaratnam, Sumirtha; Beals, Nathan; Basu, Soumitra
Abstract: G‐quadruplexes (GQs) are four‐stranded secondary structures formed by G‐rich nucleic acid sequence(s). DNA GQs are present abundantly in the genome and affect a wide range of processes associated with DNA. Recent studies show that RNA GQs are present in different transcripts, including coding and noncoding areas of mRNA, telomeric RNA as well as in other premature and mature noncoding RNAs. When present at specific locations within the RNAs, GQs play important roles in key biological functions, including the regulation of gene expression and telomere homeostasis. RNA GQs regulate pre‐mRNA processing, such as splicing and polyadenylation. Evidently, among other processes, RNA GQs also control mRNA translation, miRNA and piRNA biogenesis, and RNA localization. The regulatory mechanisms controlled by RNA GQs mainly involve binding to RNA binding protein that modulate GQ conformation or serve as an entity in recruiting additional protein regulators to act as a block element to the processing machinery. Here we provide an overview of the ever‐increasing number of discoveries revealing the role of RNA GQs in biology and their relevance in human diseases and therapeutics. This article is categorized under: RNA Structure and Dynamics > Influence of RNA Structure in Biological Systems RNA in Disease and Development > RNA in Disease Abstract : RNA G‐quadruplexes regulate cellular processes and are linked to various diseases.